تقييم دقة أشعة الانزياحات عند تحديد التشوهات الأفقية - القاموع, أديب محمود (Latakia University Journal -Engineering Sciences Series, 2019)
تتعرض المنشآت الهندسية طيلة فترة التنفيذ والاستثمار، بشكل عام ، إلى تشوهات أفقية وشاقولية . تم التطرُق في هذا البحث إلى دراسة مفهوم تقييم دقة تحديد أشعة الانزياحات الأفقية فقط .وذلك عند دراسة التشوهات في المنشآت الهندسية ، وتم تحديد الأخطاء المتوسطة التربيع لأشعة الانزياحات الأفقية، باستخدام طريقتين مختلفتين . الطريقة الأولى : استخدمت فيها علاقة الخطأ المتوسط التربيع لتابع المتحولات المترابطة Function of Correlated Arguments . والطريقة الثانية : من خلال استخدام مصفوفة معاملات الارتباط Matrix of Coefficient of Correlation لأشعة الانزياحات ، والتي ينظر إليها كمجموعة من القيم العرضية . وخلُص البحث إلى بعض الاستنتاجات والتوصيات . The engineering projects are exposed for horizontal and vertical deformations, during the period of execution and exploitation. The research discussed the valuation of the accuracy of the horizontal shifting only during examination of the deformations of the engineering projects It determined the average square errors of the horizontal shifts vectors, which were determined in two different ways. The first way is by using the formula for the average square error of the function of correlated arguments. The second way is by deducting the matrix of coefficient of correlation for the shifts vectors, which are viewed as a system of accidental quantities. The research has some conclusions and recommendations.